A series of 1,2,3-triazole compounds: Synthesis, characterization, and investigation of the cholinesterase inhibitory properties via in vitro and in silico studies - Tan, Ayşe; Almaz, Z. (Elsevier B.V., 2023)
A series of 1,2,3-triazole compounds derived from a salicylaldehyde moiety were synthesized in high yields using copper (I)-catalyzed azide-alkyne cycloaddition (CuAAC) reactions. The structures of the newly synthesized 1,2,3-triazole compounds were characterized by FT-IR, NMR, and HRMS analyses. The inhibitory activities of all the target compounds were investigated against electric eel acetylcholinesterase (eeAChE) and equine serum butyrylcholinesterase (eqBChE) enzymes. The activity results were compared with galantamine used as a reference compound. The in vitro biological assays showed that most of the target compounds had quite good inhibition activities for eeAChE, while weaker towards eqBChE. Among them, compound 23f exhibited better activity than both other target compounds and galantamine against both eeAChE (IC50: 0.458 µM) and eqBChE (IC50:1.721 µM). Molecular docking studies of all target compounds were performed on the 3D crystallographic structures of eeAChE, Homo sapiens AChE, and BChE enzymes. The binding energies appear to be consistent with the activity results. Moreover, it was determined that 23f interacted with crucial residues of the catalytic active site (CAS) and peripheral anionic site (PAS) of both AChE and BChE due to its dual binding feature. Finally, in silico ADME and toxicity properties of the compounds were investigated using the Swiss ADME and ProTox-II websites. The compounds have appropriate drug-likeness scores, Additionally, it has been estimated that 23f, the most active compound, and 23c are within the best limits in terms of oral bioavailability and exhibit low levels of toxicity. Consequently, the target compounds, especially 23f, can be considered promising inhibitors for the cholinesterase enzymes. © 2022 Elsevier B.V.
Keywords: 1,2,3-triazole; acetylcholinesterase; butyrylcholinesterase; CAS; molecular docking; PAS; salicylaldehyde; Binding energy; Biochemistry; Copper compounds; Molecular modeling; Toxicity; 1,2,3-triazole; Acetylcholinesterase; Butyrylcholinesterase; Catalytic active sites; In-silico; In-vitro; Molecular docking; Peripheral anionic site; Salicylaldehyde; Target compound; Enzymes